2003
DOI: 10.1081/pdt-120024697
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Aqueous Film Coating Process on the Properties and Stability of Tablets Containing a Moisture‐Labile Drug

Abstract: The effects of an aqueous film coating process on the morphology and storage stability of hydroxypropyl methylcellulose-coated tablets containing a moisture-labile model drug (acetylsalicylic acid, ASA) were evaluated using an instrumented side-vented tablet pan coater. Coating parameters studied were inlet air absolute humidity 5 g/m3 and 12 g/m3, spraying air pressure 100 kPa and 500 kPa, pan air temperature 35 degrees C and 55 degrees C, and coating solution flow rate 2.2 g/min and 7.8 g/min. The surface ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Ruotsalainen et al,6 who determined that film surface roughness increased with an increase in liquid supply rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruotsalainen et al,6 who determined that film surface roughness increased with an increase in liquid supply rate.…”
Section: Introductionmentioning
confidence: 99%
“…Not often explored are the roles that the spray and its characteristics play on film coat quality. Studies that do relate film coat quality to spray characteristics are: Kim et al1 and Rowe and Forse,2 who reported that incidences of logo infilling (bridging) increased as liquid supply rate increased. Twitchell,3 Twitchell et al,4 and Reiland and Eber,5 who found that increasing the atomizing air pressure or decreasing the gun‐to‐target distance resulted in a smoother film coat. Twitchell,3 who noted that a decrease in gun‐to‐target distance decreased film surface roughness. Ruotsalainen et al,6 who determined that film surface roughness increased with an increase in liquid supply rate. Fisher and Rowe7 and Rowe,8 who observed that film‐to‐tablet adhesion decreased as liquid viscosity increased. Twitchell3 and Rowe and Forse,9 who found that increasing the local spray mass flux at the tablet bed, achieved by increasing the liquid supply rate or changing the spray pattern from elliptical to circular, decreased the incidence of film splitting. …”
Section: Introductionmentioning
confidence: 99%
“…Polymeric film coatings have been applied to various solid dosage forms to improve aesthetic qualities (Felton & Wiley, 2003), mask an unpleasant odor or taste (Cerea, Zheng, Young, & McGinity, 2004;Pearnchob, Siepmann, & Bodmeier, 2003), facilitate swallowing upon ingestion, improve product stability (Felton & Timmins, 2006;Ruotsalainen, Heinamaki, Taipale, & Yliruusi, 2003), and alter drug release characteristics (Dashevsky & Mohamad, 2006;Siepmann, Siepmann, Walther, MacRae, & Bodmeier, 2006;Zheng, Sauer, & McGinity, 2005). The process of applying thin polymer films to solid substrates is a complex, multi-step process involving the atomization of the polymer solution or dispersion, the impingement of the polymer-containing droplets onto the solid surfaces, spreading of the droplets, and finally film coalescence (Carlin, Li, & Felton, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At one extreme, a high spray rate may cause coating defects such as twinning, picking and sticking, and logo bridging (18), whereas at the other extreme, a low spray rate may cause spray drying and a loss in coating efficiency. Spray rates are especially important if the tablet formulation or API is moisture-sensitive as residual water content in the coated tablets has been shown to be directly related to the spray rate (12). The rate at which the coating formulation is applied to the tablets influences the bed temperature and, thus, the rate of solvent evaporation.…”
Section: Spray Ratementioning
confidence: 99%
“…For example, it is well known that a relatively dry environment can result in tablet defects such as surface roughness, whereas a wet environment can cause tablets to stick or pick and, in extreme cases, actually dissolve during the coating process. The appearance and residual water content of coated tablets have been shown to be a direct function of coating conditions, specifically inlet air temperature and humidity, and spray rate (12). The humidity and temperature inside the pan are critical to solvent evaporation and film formation, especially with polymeric dispersions (13).…”
Section: Introductionmentioning
confidence: 99%